ANALISIS KESESUAIAN PESERTA DIDIK KELAS VI DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA ALJABAR DITINJAU DARI TAHAPAN POLYA - Nur Maharani, Maulida; Maghfirotun Amin, Siti; Hartatik, Sri; Nafiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the difficulties faced by sixth-grade students at UPT SD Negeri 150 Gresik in solving mathematical word problems based on George Polya's problem-solving framework. This research dynamic employs a qualitative descriptive approach involving 19 students, with 6 key informants selected across high, medium, and low ability levels. Data collection techniques included diagnostic tests on algebraic word problems and in-depth interviews. The results revealed that students' difficulties in solving mathematical word problems stem from both cognitive and non-cognitive factors. Cognitively, students with low ability experienced comprehension, transformation, and process skill errors due to weak foundational numeracy, such as incorrect borrowing execution in subtraction and dependency on manual repetitive addition instead of vertical multiplication algorithms. Non-cognitively, time anxiety caused high-ability students to bypass formal documentation of